Design and implementation of smart waste bin for office place - Haque, Md Fuad Fahimul; Monon, Seeam; Rahman, Tasnia; Rashid, MD Naimur (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.